A descriptive analysis of anglicisms used in ecuadorian magazines - Aguirre Retamal, Franco Carlos (2012)
The aim of the following research is focused on the linguistic phenomenon of anglicisms. The main objective of this investigation is to analyze the anglicisms used in Ecuadorian magazines. The present study took place in Quito, Ecuador. A careful selection of magazines, published and edited in Ecuador, specifically in Quito city, was done to establish the main sample of this investigation. These samples were divided into three main types of publications: cultural magazines, scholarly magazines, and general interest magazines. The results obtained from this research showed that the kind of magazine with the highest number of anglicisms in it was the general interest. The second magazine with high number of anglicisms was the cultural magazine. Finally, the magazine that shows the lowest number of anglicisisms in it was the scholarly magazine. About the most frequent anglicisms found in this study, we must state that the most popular were related to the area of music and the world of computers. Words like rock, web, jazz, estándar, punk, bar, dólares, video, CD and rol, were the most frequently found along this research.